Validation of cone-beam computed tomography and magnetic resonance imaging of the porcine spine: a comparative study with multidetector computed tomography and anatomical specimens - Costa de Freitas, Ricardo Miguel; Andrade, Celi Santos; Mendes Pereira Caldas, Jose Guilherme; Kanas, Alexandre Fligelman; Cabral, Richard Halti; Tsunemi, Miriam Harumi [UNESP]; Cervantes Rodriguez, Hernan Joel; Rabbani, Said Rahnamaye (Elsevier B.V., 2015)
BACKGROUND CONTEXT: New spinal interventions or implants have been tested on ex vivo or in vivo porcine spines, as they are readily available and have been accepted as a comparable model to human cadaver spines. Imaging-guided interventional procedures of the spine are mostly based on fluoroscopy or, still, on multidetector computed tomography (MDCT). Cone-beam computed tomography (CBCT) and magnetic resonance imaging (MRI) are also available methods to guide interventional procedures. Although some MDCT data from porcine spines are available in the literature, validation of the measurements on CBCT and MRI is lacking.PURPOSE: To describe and compare the anatomical measurements accomplished with MDCT, CBCT, and MRI of lumbar porcine spines to determine if CBCT and MRI are also useful methods for experimental studies.STUDY DESIGN: An experimental descriptive-comparative study.METHODS: Sixteen anatomical measurements of an individual vertebra from six lumbar porcine spines (n=36 vertebrae) were compared with their MDCT, CBCT, and MRI equivalents. Comparisons were made for the absolute values of the parameters. RESULTS: Similarities were found in all imaging methods. Significant correlation (p<.05) was observed with all variables except those that included cartilaginous tissue from the end plates when the anatomical study was compared with the imaging methods.CONCLUSIONS: The CBCT and MRI provided imaging measurements of the lumbar porcine spines that were similar to the anatomical and MDCT data, and they can be useful for specific experimental research studies.
Keywords: Anatomy; Porcine; Lumbar spine; Cone-beam computed tomography; Multidetector computed tomography; Magnetic resonance imaging